Avaliação dos níveis de vibração no operador de um trator agrícola ensaiado em pista normatizada em diferentes velocidades de deslocamento - Moraes, Guilherme Aparecido Gomes de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The brazilian agriculture mechanization has grown increasingly in recent decades. As a result of mechanization, great care for safety of agricultural machine operators must be present, as these vehicles expose workers to various risks, such as physical risks related specifically to the vibration of the equipment. This study aimed to evaluate the vibration levels in an agricultural tractor tested on standard roadway at different speeds accomplished in Agricultural Sciences Faculty of UNESP in Botucatu. Was used a farm tractor with 92 kW of power, and the parameters evaluated in this research were vibration dose value, equivalent power level measurement (RMS) maximum, medium and minimum acceleration resulting in 3 axes (x, y, and z), maximum peak level during the measurement, crest factor normalized acceleration and total for workday of eight hours. The data acquisition was performed with vibration recorder HVM100. The proposed data were evaluated in four forward speeds (V1=2.5 km/h, V2=3.0 km/h, V3=3.6 km/h and V4=4.4 km/h). The data were statistically analyzed using ANOVA overall comparison to one criterion and when the analysis showed statistical significance was performed an individual analysis compared by Tukey test ( p<0.05). It was observed that vibration dose values increased with increase of the speed. The x-axis was the one that presented highest vibration dose values. Values of maximum and minimum acceleration, acceleration equivalent weighted and the weighted average acceleration had their highest values at V=4.4 km/h

A mecanização na agricultura brasileira vem crescendo, cada vez mais, ao longo das últimas décadas. Como consequência dessa mecanização, o cuidado com a segurança em relação aos operadores de máquinas agrícolas deve estar presente, já que esses veículos expõem o trabalhador a uma série de riscos, tais como: físicos, químicos, biológicos, ergonômicos de acidentes e, especificamente, os relacionados às vibrações do equipamento. O presente trabalho teve como objetivo comparar os níveis de vibração em um trator agrícola ensaiado em pista normatizada em diferentes velocidades de deslocamento. O experimento foi conduzido nas dependências da Faculdade de Ciências Agronômicas/UNESP no Campus de Botucatu-SP. Empregou-se um trator agrícola de 92 kW de potência e os parâmetros avaliados foram: valor da dose de vibração, nível de energia equivalente da medição, níveis máximo, médio e mínimo de aceleração RMS resultantes nos 3 eixos (x, y e z), nível máximo do pico durante a medição, fator de crista total e a aceleração normalizada para jornada de trabalho de 8 horas. A aquisição dos dados foi realizada com o registrador de vibração HVM 100. As grandezas propostas foram avaliadas em quatro velocidades de deslocamento (V1=2,5 km/h, V2=3,0 km/h, V3=3,6 km/h e V4=4,4 km/h). Os dados foram analisados estatisticamente por meio de comparação global ANOVA a um critério e quando a análise apresentou diferença estatística realizouse uma comparação individual por meio do teste de Tukey (p<0,05). Observou-se que os valores de dose de vibração foram crescentes com o aumento da velocidade de ...
Evaluation of vibration levels in an operator of agricultural tractor tested in standardized track at different speeds of displacement
Keywords: Mecanização agrícola; Tratores agricolas - Vibração; Saúde do trabalhador; Insalubridade; Mechanization